The current understanding of the biology of the SARS-CoV-2 virus - Palese, Peter (Henry Stewart Talks, 2020)
Comparison between this new SARS-COV-2 strain and other coronavirus strains, What information we are currently missing, Steps in how to obtain required knowledge, The current knowledge on methods of transmission, A future view on therapies and vaccination